Impact Assessment of European Structural Funds in Andalusia - a CGE Approach - M. Carmen Lima; M. Alejandro Cardenete (European Regional Science Association (ERSA), 2005)
In this work we carry out an impact analysis of the European Structural Funds (ESF) to the object of assessing their effect on the GDP, the level of prices or the consumers' income on the region of Andalusia in the south of Spain. Accordingly, we present an Applied General Equilibrium Model (AGEM_A) and we compare the reception scenario of regional funds with a hypothetical situation where this financial support has been removed. The AGEM_A has been built by supplementing the statistical information provided by the Social Accounting Matrices for Andalusia corresponding to 1990, 1995 and 1999, with the data included in the three Community Support Frameworks (CSF) approved by the European Commission.
Keywords: 330